2018
DOI: 10.4103/jomfp.jomfp_216_17
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and correlation of lip print, palm print, fingerprint pattern and blood group in twin population

Abstract: Background: Twins are similar in many ways owing to the genetical and environmental factors. However, still, there are certain things that are not similar among them, and this is the challenge for personal identification among the twins. Objectives: Our present study aimed to know and assess the similarities and differences present between the monozygotic (identical) and dizygotic (fraternal) twins in relation to lip prints, palm prints, fingerprints and blood group and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…6,7 Dermatoglyphics is the scientific study of epidermal ridges and their configuration on the volar aspect of the palmar and plantar regions. 8 The palmar surfaces of hands have friction ridges known as papillary or epidermal ridges. The establishment of these epidermal ridges takes place from the 10 th to 16 th weeks of development.…”
mentioning
confidence: 99%
“…6,7 Dermatoglyphics is the scientific study of epidermal ridges and their configuration on the volar aspect of the palmar and plantar regions. 8 The palmar surfaces of hands have friction ridges known as papillary or epidermal ridges. The establishment of these epidermal ridges takes place from the 10 th to 16 th weeks of development.…”
mentioning
confidence: 99%
“…Biological babies constitute a peculiarity inherent to cheiloscopy. 17,18,19 The data of the present study also proved very helpful to see if there is any correlation of the lip print types with gender. There are several studies available that showed the relationship of type II lip print either with male or female while other studies showed the lip print type IV as most common in both sexes.…”
Section: Discussionmentioning
confidence: 56%
“…In the study by Venkatesh and David [ 5 ], the highest bias risk was assigned, because only one characteristic of the participants was mentioned. In the domain referring to methodology, the use of the modified S&T classification, considered not fully valid, contributed to the attribution of the medium bias risk in two studies [ 15 , 20 ]. In domains 5 and 6, most articles did not mention if any strategy was used to evaluate inter- and intra-rater reliability.…”
Section: Resultsmentioning
confidence: 99%
“…At the lowest level of bias risk are the last two studies. In the study by Debta et al, a statistically significant association was found between lip prints of monozygotic twins and those of their parents ( p = 0.02) as well as between lip prints of dizygotic twins and those of their parents ( p = 0.03), indicating the existence of heredity according to the authors [ 20 ]. In the study by Loganadan et al, 53.33% of the children’s prints showed similarities to their fathers’ lip prints and 73.33% to their mothers’ prints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation